Copenhague en el papel - Ros de Olano, Ignacio (2009)
Comentarios sobre la historia urbana y arquitectónica de la capital danesa.
Keywords: DINAMARCA; KØBENHAVN; COPENHAGUE; URBANISMO; CIUDADES; ARQUITECTURA; HISTORIA